1972
DOI: 10.1111/j.1365-2478.1972.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Time, Frequency, and Phase Measurements in Induced Polarization*

Abstract: In comparing the similarity between time, frequency, and phase measurements as used in the induced polarization method of geophysical prospecting, parameters must first be defined and the basis for comparison established. The conditions for mathematical equivalence then follow in a natural sequence. Laboratory measurements are made on a variety of rock samples to indicate the type of comparison and correlation expected from field measurements. Results indicate that frequency domain and phase measurements are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 2 publications
0
12
0
2
Order By: Relevance
“…Inversion results are shown together with background geological information and it is concluded that they are in good agreement.In near-surface applications induced polarization has shown to be especially useful for delineating landfills (e.g., Carlson et al 1999;Iliceto et al 1999;Dahlin et al 2010), mapping pollutant plumes (e.g., Abu-Zeid et al 2004;Sogade et al 2006) and in hydrogeological applications (e.g., Martinho andAlmeida 2006), where one hopes to be able to estimate hydraulic conductivity (e.g., Hördt et al 2007).Induced polarization can be quantified using a number of different parameters, e.g., chargeability in the time domain, frequency effect, phase and amplitude in the frequency domain. Although comparable, these measurements are not strictly equivalent (e.g., Zonge et al 1972). Comparing results obtained at different sites with different measuring equipment can as a Our expertise covers mineral exploration, all types of near surface surveys, marine geophysics, UXO and surveys for other manmade hazards…”
mentioning
confidence: 83%
“…Inversion results are shown together with background geological information and it is concluded that they are in good agreement.In near-surface applications induced polarization has shown to be especially useful for delineating landfills (e.g., Carlson et al 1999;Iliceto et al 1999;Dahlin et al 2010), mapping pollutant plumes (e.g., Abu-Zeid et al 2004;Sogade et al 2006) and in hydrogeological applications (e.g., Martinho andAlmeida 2006), where one hopes to be able to estimate hydraulic conductivity (e.g., Hördt et al 2007).Induced polarization can be quantified using a number of different parameters, e.g., chargeability in the time domain, frequency effect, phase and amplitude in the frequency domain. Although comparable, these measurements are not strictly equivalent (e.g., Zonge et al 1972). Comparing results obtained at different sites with different measuring equipment can as a Our expertise covers mineral exploration, all types of near surface surveys, marine geophysics, UXO and surveys for other manmade hazards…”
mentioning
confidence: 83%
“…where ρ a (f l ) and ρ a (f h ) are Cagniard apparent resistivity at the low frequency f l and at the high frequency f h , respectively. According to Zonge et al [15] ,the PFE calculated by the amplitude at both the high frequency f h and the low frequency f l is approximatively proportional to the phase ϕ(f a ) of the geometrical middle frequency f a between the two frequencies…”
Section: Numerical Modeling Resultsmentioning
confidence: 99%
“…where Therefore Zonge et al [15] concluded that the PFE acquired by the two frequency measurement could be replaced by the phase measurement of a single frequency. However, the impedance phase calculated in this study is just directly proportional to the PFE calculated by the impedances (actually, i.e.…”
Section: Numerical Modeling Resultsmentioning
confidence: 99%
“…), such as amplitude and phase measurements made on rock samples containing disseminated sulfide mineralization. For this purpose, the phase and normalized voltage measurements from the sample MINN-2 published by Zonge et al (1972) are used as an example. These data have been digitized and listed in Table 1 together with the measured current density, the sample length, as well as the resistivity values measured at lo-' and lo3 Hz, respectively.…”
Section: Electrochemical and Electromagnetic Effectsmentioning
confidence: 99%